Mats of psychrophilic thiotrophic bacteria associated with cold seeps of the Barents Sea - S. Grünke; A. Lichtschlag; D. de Beer; J. Felden; V. Salman; A. Ramette; H. N. Schulz-Vogt; A. Boetius (Biogeosciences, 2012)
This study investigated the bacterial diversity associated with microbial mats of polar deep-sea cold seeps. The mats were associated with high upward fluxes of sulfide produced by anaerobic oxidation of methane, and grew at temperatures close to the freezing point of seawater. They ranged from small patches of 0.2–5 m in diameter (gray mats) to extensive fields covering up to 850 m2 of seafloor (white mats) and were formed by diverse sulfide-oxidizing bacteria differing in color and size. Overall, both the dominant mat-forming thiotrophs as well as the associated bacterial communities inhabiting the mats differed in composition for each mat type as determined by microscopy, 16S rRNA gene sequencing and automated ribosomal intergenic spacer analysis. While the smaller gray mats were associated with a highly diverse composition of sulfide oxidizers, the larger white mats were composed of only 1–2 types of gliding Beggiatoa filaments. Molecular analyses showed that most of the dominant mat-forming sulfide oxidizers were phylogenetically different from, but still closely related to, thiotrophs known from warmer ocean realms. The psychrophilic nature of the polar mat-forming thiotrophs was tested by visual observation of active mats at in situ temperature compared to their warming to >4 °C. The temperature range of mat habitats and the variation of sulfide and oxygen fluxes appear to be the main factors supporting the diversity of mat-forming thiotrophs in cold seeps at continental margins.